Lawyers and children: Is there a need for mandatory legal assistance in suspect interviews? - Schoovaerts, Hanne (International journal of police science & management, 2021)
In 2016, Belgium introduced legislation mandating legal assistance for juvenile suspects. However, legal assistance can only serve as an effective procedural safeguard if it is provided appropriately. The current study examined how lawyers in Belgium fulfil this role in practice. Seventeen video-recorded police interviews of juvenile suspects were observed. The juveniles were aged between 12 and 17 years, and were suspected of various less serious, volume crimes. The findings of this study show that the ‘law in action’ does not always reflect the ‘law in the books’. The mere presence of a lawyer is insufficient: it is necessary for them to actively engage. Although police interviewers typically adopt an information-gathering approach, some interviews do require the lawyer’s intervention to protect the juvenile’s interests. Moreover, lawyers often restrict themselves to ‘legal’ assistance and offer limited (emotional) support. Because there is no ‘appropriate adult’ regime in Belgium, lawyers could take up this double role. The information-gathering approach also seems to enhance cooperation between lawyer and interviewer, resulting in a joint search for the truth in which neither adopts an antagonistic role when interviews are conducted properly.